2021
DOI: 10.3390/atmos12060659
|View full text |Cite
|
Sign up to set email alerts
|

Local Analysis of Air Quality Changes in the Community of Madrid before and during the COVID-19 Induced Lockdown

Abstract: This paper examines the effect of the COVID-19 induced lockdown upon six pollutants, CO, NO, NO2, PM10, PM2.5, and O3, in the Spanish community of Madrid. The paper relies on clustering methods and multiple regression techniques to control for a battery of potential confounding factors. The results show that the nationwide lockdown, decreed on 13 March by the Spanish government, exerted a statistically significant effect upon most pollution indicators. The estimates range from approximately −82% (NO and NO2) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
3
13
1
Order By: Relevance
“…This time frame corresponds to those weeks with the most strict restrictions for the civilian population in Spain. Previous research work has demonstrated the improvements in air quality due to the lockdown of the COVID-19 pandemic [18][19][20][21][22]. All sources agree on a reduction on the levels of NO 2 ; therefore, it can be considered as a verified event able to validate the method presented.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…This time frame corresponds to those weeks with the most strict restrictions for the civilian population in Spain. Previous research work has demonstrated the improvements in air quality due to the lockdown of the COVID-19 pandemic [18][19][20][21][22]. All sources agree on a reduction on the levels of NO 2 ; therefore, it can be considered as a verified event able to validate the method presented.…”
Section: Resultsmentioning
confidence: 77%
“…The behavior of these pollutants during the lockdown of the COVID-19 pandemic has been studied by previous research [18][19][20][21][22]. All sources concur on a reduction of the NO 2 levels.…”
Section: Case Study -Air Quality In Gijon Spainmentioning
confidence: 97%
See 2 more Smart Citations
“…In the MRSP, ~90 km of congested roads were estimated every day in 2019. It was expected that the reduction of congestion during COVID-19 months due to confinement measures may affect the air quality significantly [41][42][43][44].…”
Section: Covid-19 Scenariosmentioning
confidence: 99%